Ratio Legis Pemilihan Kepala Daerah dalam Perspektif Konsep Dasar Pemilihan Umum - Isnayanti Isnayanti (Jurnal Ilmu Sosial dan Humaniora, 2026)
Regional Head Elections are one of the mechanisms for implementing popular sovereignty in Indonesia's democratic system. However, there remains debate regarding the status of Regional Head Elections, whether they fall within the General Election regime as stipulated in Article 22E of the 1945 Constitution of the Republic of Indonesia or within the regional government regime as stipulated in Article 18 paragraph (4). This study aims to analyze the legal ratio of Regional Head Elections from the perspective of the basic concepts of General Elections. The research method used is normative legal research with a regulatory, historical, and contextual approach. The results indicate that substantively, Regional Head Elections share similar principles with General Elections, both in terms of principles, organizers, participants, stages, and dispute resolution mechanisms. Therefore, conceptually, Regional Head Elections can be understood as part of General Elections in the implementation of popular sovereignty.